2011
DOI: 10.1007/s13174-011-0050-y
|View full text |Cite
|
Sign up to set email alerts
|

On understanding the economics and elasticity challenges of deploying business applications on public cloud infrastructure

Abstract: The exposure of business applications to the web has considerably increased the variability of its workload patterns and volumes as the number of users/customers often grows and shrinks at various rates and times. Such application characteristics have increasingly demanded the need for flexible yet inexpensive computing infrastructure to accommodate variable workloads. The on-demand and per-use cloud computing model, specifically that of public Cloud Infrastructure Service Offerings (CISOs), has quickly evolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 23 publications
2
22
0
4
Order By: Relevance
“…Thus, an elasticity capability defines what resource, cost, quality or associations among services can be created, when (instantiation or run time), and how often the services can be reconfigured. By studying main cloud providers, such as Amazon EC2 2 , Rackspace 3 , HPCloud 4 , and Windows Azure 5 , and through other studies [11], we found that elasticity capabilities of cloud services indicate which types of configurations are available and in which phases of the service's life-cycle. While some providers give hints about the capabilities of their services, (e.g., Amazon EC2 spot instances can be replaced faster than reserved instances), existing tools do not capture and evaluate such capabilities.…”
Section: Modeling Elasticity Capabilities Of Cloud Servicesmentioning
confidence: 85%
“…Thus, an elasticity capability defines what resource, cost, quality or associations among services can be created, when (instantiation or run time), and how often the services can be reconfigured. By studying main cloud providers, such as Amazon EC2 2 , Rackspace 3 , HPCloud 4 , and Windows Azure 5 , and through other studies [11], we found that elasticity capabilities of cloud services indicate which types of configurations are available and in which phases of the service's life-cycle. While some providers give hints about the capabilities of their services, (e.g., Amazon EC2 spot instances can be replaced faster than reserved instances), existing tools do not capture and evaluate such capabilities.…”
Section: Modeling Elasticity Capabilities Of Cloud Servicesmentioning
confidence: 85%
“…Vários autores concordam quanto à divisão de elasticidade horizontal e vertical para essa classificação [13,14,15,16]. Na horizontal é possível aumentar ou diminuir o número de instâncias (MVs), assim como é possível sua migração para novos nós de processamento.…”
Section: Modalidadeunclassified
“…The economic implications of elasticity for service providers have been analyzed in [16] [17], where the result of the elasticity feature of a cloud platform is measured by a single valued metric based on (monetary) costs. Such an approach has also been taken in [18] and extended by [19].…”
Section: Related Workmentioning
confidence: 99%